2022
DOI: 10.3389/fpsyg.2022.818967
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Sudden Sensorineural Hearing Loss in Different Ages: Prognosis of Patients With Initial Total Hearing Loss

Abstract: ObjectiveThis study aimed to analyze the hearing improvement and prognosis factors of idiopathic sudden sensorineural hearing loss (ISSNHL) in different ages with initial total hearing loss.MethodsWe reviewed the medical records of 5,711 hospitalized patients with ISSNHL from 2016 to 2021 in our center. All of the patients had been treated with uniform combination drug therapy. After excluding the patients with initial partial hearing loss and those diagnosed with clear etiology, 188 patients were enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
4
1
1
Order By: Relevance
“…Cogan’s syndrome, a rare autoimmune disease primarily affecting young adults, is marked by non-syphilitic interstitial keratitis and audio-vestibular symptoms; in particular, SSNHL, irrespective of its association with vestibular symptoms, can be the initial manifestation of this syndrome [ 19 ]. Although some authors have suggested that younger age is a favorable prognostic factor for SSNHL [ 20 , 21 , 22 , 23 ], our data showed that only one in five patients had complete recovery of the HT. In detail, this study revealed that factors such as age and sex did not have a significant impact on the likelihood of having HT improvement or severe-to-profound HL at the audiological evaluation after one year.…”
Section: Discussioncontrasting
confidence: 88%
“…Cogan’s syndrome, a rare autoimmune disease primarily affecting young adults, is marked by non-syphilitic interstitial keratitis and audio-vestibular symptoms; in particular, SSNHL, irrespective of its association with vestibular symptoms, can be the initial manifestation of this syndrome [ 19 ]. Although some authors have suggested that younger age is a favorable prognostic factor for SSNHL [ 20 , 21 , 22 , 23 ], our data showed that only one in five patients had complete recovery of the HT. In detail, this study revealed that factors such as age and sex did not have a significant impact on the likelihood of having HT improvement or severe-to-profound HL at the audiological evaluation after one year.…”
Section: Discussioncontrasting
confidence: 88%
“…We did not find data in the literature on EHF audiometry in SSNHL for comparison, as the studies only evaluated standard PTT audiometry and reported recovery of auditory thresholds in 51%, 43%, and 78%, respectively (8,37,41), after 1 month of treatment. Such difference in recovery rate may result from a spectrum of varying clinical and phenotypic characteristics not shown if relying solely on standard PTT audiometry.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical audiometer-AC40 and the tympanometer-AT235h (Interacoustics A/S, Denmark) were used. When PTTs were absent, the audiometer's maximum output intensity was used: 110-110-120-120-120-120-110-100-90-95-95-80-65-65-60-60 dBHL at 250-500-1,000-2000-3,000-4,000-6,000-8,000-9,000-10,000-11,000-12,000-13,000-14,000-15,000-16,000 Hz, respectively, for air conduction and 70 dBHL for bone conduction (36,37).…”
Section: Instruments Appliedmentioning
confidence: 99%
“…There are many hypotheses about the pathogenesis of SSNHL: infectious, vascular, inflammatory, immune, degenerative, etc., ( 20 , 21 ). It is known that age, vertigo, and the time to delay treatment after onset are closely related to the degree of recovery of SSNHL ( 22 24 ). In recent years, more and more studies have suggested that cardiovascular factors, hemorheology, and oxidative stress are related to the occurrence and prognosis of SSNHL ( 25 , 26 ), specific inflammatory and cardiovascular markers have also been shown to be related to the outcome of SSNHL ( 18 , 27 30 ).…”
Section: Discussionmentioning
confidence: 99%